If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 + -1k = -15 Solving -22 + -1k = -15 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + -1k = -15 + 22 Combine like terms: -22 + 22 = 0 0 + -1k = -15 + 22 -1k = -15 + 22 Combine like terms: -15 + 22 = 7 -1k = 7 Divide each side by '-1'. k = -7 Simplifying k = -7
| 1/16(4) | | w/4-2.5=-8.9 | | 2x+5x-6=1 | | 3x-3-6=2x-10 | | 2x+15x=0 | | 6/5x-4/x=-3 | | 2x/3+4=14/3 | | 45-k=-20 | | 2x^2y+6xy-22y=0 | | 17/2n=21/2n | | 4a/5(10-25b) | | 4z-3(z-10)+6=23 | | 19-x=-22 | | 16p^2-25=0 | | 31=4x-7+2x | | u/3=u/4+3 | | -6x^2=5x+6 | | 3x(2r+8)=16 | | 1/3(2x-4)=-6 | | -3=4(x+7)-15 | | -17-k=-24 | | -3=4(x+7) | | 35n+12=40 | | 6y+y=-42 | | 9y/x=4 | | 2x^2y+6xy-22y= | | 9(y+10)=12y+15 | | -5(5x-6)=330 | | 3x+2=4x-(5-2x) | | 1/3n-11=38 | | 36-m=25 | | -(y+13)+2y-2=-7 |